2016
DOI: 10.1113/ep085627
|View full text |Cite
|
Sign up to set email alerts
|

Impaired glucose‐stimulated insulin secretion and reduced β‐cell mass in pancreatic islets of hyperthyroid rats

Abstract: New Findings r What is the central question of this study?Thyroid dysfunction can have a major impact on pancreatic function. The influence of hyperthyroidism on insulin secretion remains controversial, and the precise mechanism of its effect has not yet been elucidated. r What is the main finding and its importance?The results of this study demonstrate that hyperthyroidism leads to impaired insulin secretion. It appears that the defect in insulin secretion in the hyperthyroid state probably reflects a summati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 41 publications
0
9
0
1
Order By: Relevance
“…Treatment with high levels of T4 could induce pancreatic β cell apoptosis, as was shown by an increase in transferase-mediated deoxyuridine triphosphate-biotin nick end labeling (TUNEL) and caspase-3 expressions in rat β cells [ 89 ]. Recently, it was demonstrated that impaired glucose-stimulated insulin secretion and reduced β cell mass occurred in pancreatic islets of hyperthyroid rats [ 90 ]. The former effect may be related to decreased sensitivity of ATP-sensitive K + (K + (ATP)) and L-type Ca 2+ channels of the β cells.…”
Section: Roles Of Thyroid and Thyroid Hormone In Pancreas Pathogenmentioning
confidence: 99%
“…Treatment with high levels of T4 could induce pancreatic β cell apoptosis, as was shown by an increase in transferase-mediated deoxyuridine triphosphate-biotin nick end labeling (TUNEL) and caspase-3 expressions in rat β cells [ 89 ]. Recently, it was demonstrated that impaired glucose-stimulated insulin secretion and reduced β cell mass occurred in pancreatic islets of hyperthyroid rats [ 90 ]. The former effect may be related to decreased sensitivity of ATP-sensitive K + (K + (ATP)) and L-type Ca 2+ channels of the β cells.…”
Section: Roles Of Thyroid and Thyroid Hormone In Pancreas Pathogenmentioning
confidence: 99%
“…A reduced volume of pancreatic islets and a lower number of insulin-positive cells have been demonstrated in rats with experimentally induced hyperthyroidism. A defective insulin secretory response due to a possible defect in K ATP and L-type calcium channels was also noted [25]. Similarly, severe hyperthyroidism has also been shown to induce apoptosis of beta cells and to accelerate the rate of apoptosis of pancreatic ductal cells, which serve as precursors of beta cells.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the role of TH has been demonstrated particularly in glucose homeostasis [ 43 ]. Indeed, hyperthyroid rats showed reduced glucose tolerance and reduced insulin-secretory capacity of β cells, in addition to an increased hepatic insulin resistance [ 44 ]. Similarly, hypothyroidism promotes glucose intolerance in hypothyroid non-diabetic mice [ 45 ].…”
Section: Effects Of Th On Central Metabolismmentioning
confidence: 99%